2005
DOI: 10.1348/014466604x17948
|View full text |Cite
|
Sign up to set email alerts
|

Clearing the air: The effect of experimenter race on target's test performance and subjective experience

Abstract: According to stereotype threat theory (Steele, 1997), stereotyped targets under-perform on challenging tests, in part because they are worried about being viewed in terms of the negative stereotype that they are intellectually inferior. How then are the negative effects of stereotype threat reduced for stereotyped targets? To examine this issue, a study was conducted to investigate whether stereotype threat's adverse effects are reduced when a Black experimenter administers a verbal test to Black participants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
161
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(171 citation statements)
references
References 28 publications
7
161
2
1
Order By: Relevance
“…Empirically validated interventions include the removal of cues that trigger stereotype threat (45)(46)(47), the use of positive role models (48)(49)(50), the use of values affirmation (51)(52)(53)(54), and the emphasis on growth mindset theories about intelligence and achievement (55). Many of these interventions have been tested in controlled settings, external to the class environment, and many have yet to be applied in a large-scale, practical manner.…”
Section: Discussionmentioning
confidence: 99%
“…Empirically validated interventions include the removal of cues that trigger stereotype threat (45)(46)(47), the use of positive role models (48)(49)(50), the use of values affirmation (51)(52)(53)(54), and the emphasis on growth mindset theories about intelligence and achievement (55). Many of these interventions have been tested in controlled settings, external to the class environment, and many have yet to be applied in a large-scale, practical manner.…”
Section: Discussionmentioning
confidence: 99%
“…However, two main features of a role model are that she or he must be perceived as a primary source of influence within academic, social, career, and personal domains and that one's relation to a role model can be formal (e.g., an interpersonal introduction and subsequent meeting) or informal (e.g., reading about a person via mass media); of note, a real interaction and relational emotional closeness are not prerequisites for an individual to serve as a role model. Based on this definition, role model studies have demonstrated that the real or imagined presence of a single role model or multiple role models can ameliorate stigmatized individuals' self-perceptions and performance behaviors (Asgari, Dasgupta, & Gilbert-Cote, 2010;Lockwood, 2006;Marx & Goff, 2005;Marx & Roman, 2002;McGlone, Aronson, & Kobrynowicz, 2006;McIntyre, Paulson, & Lord, 2003;but see McIntyre et al, 2005). Consistent with the above definition and research, the present research suggests that Obama (and similarly successful African Americans) may serve as a role model to fellow African Americans.…”
Section: Implications For Literature On Role Modelsmentioning
confidence: 99%
“…We posited that intergroup dynamics play a key role both in initiating downward spirals and in determining their later trajectory. Concerning the first part of this claim, research suggests that the presence of an outgroup test administrator, experimenter, or evaluator provokes underperformance, particularly when the task is difficult and/or threatening (Baratz, 1967;Katz & Greenbaum, 1963;Marx & Goff, 2005;Rumenik, Capasso, & Hendrick, 1977). All else being equal, performance in the presence of others reflects the fact that ingroup members are sources of implicit security and outgroup members are sources of implicit threat.…”
Section: Reversing Downward Performance Spiralsmentioning
confidence: 99%